The recognition of Sowa Rigpa in India: How Tibetan medicine became an Indian medical system (Medicine Anthropology Theory, 2016)
In 2010, the Government of India officially recognized Tibetan medicine as an ‘Indian system of medicine’ called ‘Sowa Rigpa’. This article documents the processes that led to Sowa Rigpa’s recognition, and situates them at the confluence of economic interests and political strategies within a larger historical and cultural context. Recognition emerges here as a twofold process that makes Sowa Rigpa legible to the state while simultaneously facilitating its incorporation into the market as capital. Previously an inalienable part of Tibetan and Buddhist Himalayan cultural heritage, Sowa Rigpa could now be legitimately claimed or appropriated as cultural, political, or economic capital, giving rise to tensions over ownership and control. Tracing how Sowa Rigpa’s recognition transformed from an initial struggle for protection to one over control, this article offers a critical new perspective on the recognition of cultural heritage, India’s pluralistic health care system, and the Asian traditional pharmaceutical industry.